Moisture stress at critical stages of rice (Oryza sativa) hampers grain yield and economics by inhibiting the growth and yield-forming traits - PATNAIK, GIRIJA PRASAD; THAVAPRAKAASH, N; SACHIN, S SACHIN3 (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted during rainy (kharif) (July–November) 2019 and late winter (rabi) (December–March) 2019–20 seasons at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to evaluate the effect of moisture stress (MS) at critical stages on the production and economics of rice (Oryza sativa L.). Eight MS treatments, viz. MS for 10 days from panicle initiation (PI) stage (T1); MS for 15 days from PI stage (T2); MS for 20 days from PI stage (T3); MS for 25 days from PI stage (T4); MS for 10 days from flowering stage (T5); MS for 15 days from flowering stage (T6); MS for 20 days from flowering stage (T7); and MS for 25 days from flowering stage (T8) were compared with the irrigated control (SRI method, T9) in a randomized complete block design (RCBD) with three replications. Two-season pooled mean results revealed that MS imposed at the PI stage had a more detrimental effect on rice growth, yield attributes, yield, and economic parameters than the flowering stage. Specifically, MS for 20 and 25 days at PI stage (T3 and T4) resulted in a higher penalty of grain yield (56.2 and 58.0%, respectively) and straw yield (33.2 and 36.4%, respectively) and economic parameters (gross return, net return, and benefit-cost ratio) due to hampered growth and subsequent deterioration in yield attributes of rice. Hence, the study concludes that moisture stress at the panicle initiation stage generally, and more precisely, for 20–25 days at the panicle initiation stage is highly detrimental to rice causing growth, yield attributes, yield, and economic parameters.